The Places Where Community Is Practiced : How Store Owners and Their Businesses Build Neighborhood Social Life - Steigemann, Anna (Wiesbaden Springer Nature, 2019)
In this open access publication, the social cohesion of urban neighborhoods and their residents is examined, which is often viewed as vulnerable since increased mobility, individualization, wider socio-economic and demographic changes have fundamentally altered the basis for everyday social interaction in urban neighborhoods. Anna Steigemann gives scholarly attention to the concrete places where neighborly interactions still take place and to how these interactions affect local community building. She illuminates and explores the ordinary everyday interactions and social practices in and around shops and gastronomic facilities on a shopping street in Berlin-Neukölln, revealing how these businesses are important places where community is practiced, but also why they are increasingly threatened by commercial and residential gentrification.
English
Keywords: Sociology; Human geography; Urban & municipal planning; Social sciences; Sociology, Urban; Human geography; Urban geography